Zsazsa Zaturnnah sa kalakhang Maynila #1ng tatlong bahagi - Vergara, Carlo; Gaw, Reby; Ramirez, Nida (Pasay City Visprint, 2011)
Zsazsa Zaturnnah sa kalakhang Maynila is the sequel to the award-winning graphic novel. This is the first of three parts.
Keywords: Comic books, strips, etc. -- Philippines